Influence of body mass index on induction of labor: a historical cohort study - Dammer, Ulf; Weiß, Christel; Sütterlin, Marc (The journal of obstetrics and gynaecology research, 2018)
Aim We aimed to determine the influence of body mass index (BMI) on induction of labor. Methods In this historical multicenter cohort study, 2122 labor inductions were analyzed. Women were divided into four groups according to their body mass index (BMI): BMI < 30 (normal group [NG]), 30 ≤ BMI < 35 (group 1 [G1]), 35 ≤ BMI < 40 (group 2 [G2]), and BMI ≥ 40 (group 3 [G3]). The primary outcome measure was the induction-to-delivery interval. The secondary outcome parameter was, among others, the rate of cesarean section. Results A total of 1113 inductions of labor were analyzed in the NG, 610 in G1, 239 in G2, and 160 in G3. The induction-to-delivery interval was shorter in the NG compared to G1 (mean values 1550 min vs 1669 min, P = 0.0406), G2 (1745 min, P = 0.0294), and G3 (1899 min, P = 0.0008). The cesarean section rate was significantly higher in G1-G3 (G1: 30.8%, P < 0.001; G2: 30.5%, P < 0.0067; G3: 42.5%, P < 0.0001) compared to the NG (21.8%). There were more vaginal deliveries within 48 h in the NG (84%) compared to G1-G3 (78%, P = 0.0186; 75%, P = 0.0049; 75%, P = 0.0329). However, these findings could mainly be seen in nulliparous women when stratifying for parity. Multivariable analysis showed that high BMI increased the induction-to-delivery interval whereas high parity, gestational age, and Bishop score decreased it. Conclusion An increased body mass index has a negative impact on induction of labor at term, especially in nulliparous women.
Gesehen am 25.07.2019